COMPARISON OF LAND SURFACE HYDROLOGY IN REGIONAL CLIMATE SIMULATIONS OF THE BALTIC SEA CATCHMENT - Van Den Hurk B.J.J.M.; Graham L.P.; Viterbo P. (My University, 2002)
Simulations with a regional climate model RACMO were carried out over the catchment area of the Baltic Sea for the growing season 1995. Two different surface schemes were included which in particular differed with respect to the parameterization of runoff. In the first scheme (taken from ECHAM4), runoff is a function of the subgrid distribution of the soil moisture saturation. In the second model (taken from ECMWF), runoff is a result of deep-water drainage. A large-scale hydrological model of the catchment, HBV-Baltic, was calibrated to river discharge data and forced with observed precipitation, yielding independent comparison material of runoff of the two RACMO simulations.The simulations showed that the temporal and spatial simulation of precipitation in the area is sensitive to the choice of the land surface scheme in RACMO. This supported the motivation of analysing the land surface hydrological budgets in a coupled mode.The comparison of RACMO with HBV-Baltic revealed that the frequency distribution of runoff in the ECMWF scheme shows very little runoff variability at high frequencies, while in ECHAM4 and HBV the snow melt and (liquid) precipitation are followed by fast responding runoff events.The seasonal cycle of soil water depletion and surface evaporation was evaluated by comparison of model scores with respect to relative humidity. Results suggest that the surface evaporation in the ECMWF scheme is too strong in late spring and early summer, giving rise to too much drying later in the season.